Darwin's religious odyssey - Phipps, William E., 1930-2010. (Harrisburg, Pa. : Trinity Press International, 2002)
Publisher's description: In the twenty-first century, Charles Darwin and his theory of evolution remain at the center of religious controversy. More than any scientific discovery, his work seems to challenge world religions and cause ordinary religious people to confront their own core values. With all we know about his ideas on geology and biology, we know much less about Darwin's own journey of faith. In Darwin's Religious Odyssey, William Phipps uses newly available material to explore the evolution of Darwin's religious outlook. It is a fascinating faith odyssey, because it mirrors the struggles of other scientists trying to harmonize their findings with their own religious worldviews. Darwin's detractors tend to depict him as an anti-religious man determined to undermine biblical faith; even some of Darwin's admirers agree. Yet Darwin's autobiography and his journals tell a much different story. It is clear that Darwin did not sail directly from Christian orthodoxy to atheistic materialism. His journals, for example, disclose an attempt to reconcile his evolutionary views with Anglican doctrines. Phipps paints the important aspect of Darwin's religious life against the background of his times. This book examines not only Darwin's changing theology but compares his religious and moral viewpoints with those of his family and associates. Phipps concludes that Darwin was both a product of his religious culture and the shaper of future scientific culture.
Preface -- Selective Darwin-Wedgwood genealogy -- Growing up Anglican -- Early religious influences ; Paley's sway over the prospective priest ; Clerical mentors and friends -- Christian voyager -- Religious perspectives in South America ; Indignation over slavery ; Challenges to theological doctrines ; Visiting Protestant missionary areas -- Unorthodox theorist -- Bible revisited ; Other religious reflections ; His eventful thirties ; Agonizing decade -- Evolutionary tree of life -- Enter Gray and Wallace ; Origin of species ; Theism affirmed -- Religious controversies over natural selection -- In Britain ; In America -- Homo sapiens creation -- Animality of humans ; Evolution of morality and religion ; Responses to The descent of man -- Final personal considerations -- Two similar Agnostics ; Latter-day religion ; Memorializing the scientific saint ; Reverent Charles Darwin -- Theological conclusions -- Design argument transformed ; Theodicy issue reformulated ; Biblical interpretation ; Darwin's religious legacy.
Includes bibliographical references (p. 202-204).
Keywords: Darwin, Charles, -- 1809-1882 -- Religion; Evolution (Biology) -- Religious aspects; Religion and science; Evolution -- Religious aspects